2017
DOI: 10.1016/j.ejpb.2017.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Secretome released from hydrogel-embedded adipose mesenchymal stem cells protects against the Parkinson’s disease related toxin 6-hydroxydopamine

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…The reintroduction of SIRT3 into AFSCs reversed cellular viability under high glucose stress. Similarly, careful studies from several researchers have confirmed that SIRT3 activation preserves the mononuclear cells mobility [55], protects adipose mesenchymal stem cells against oxidative stress [56], reduces human mesenchymal stem cells senescence by maintaining mitochondrial ROS homeostasis [57], inhibits neural stem cells death [58], promotes bone marrow cell-mediated angiogenesis in post-myocardial infarction [59]. These evidences demonstrate that SIRT3 is the potential target for enhancing stem cell viability and function.…”
Section: Discussionmentioning
confidence: 99%
“…The reintroduction of SIRT3 into AFSCs reversed cellular viability under high glucose stress. Similarly, careful studies from several researchers have confirmed that SIRT3 activation preserves the mononuclear cells mobility [55], protects adipose mesenchymal stem cells against oxidative stress [56], reduces human mesenchymal stem cells senescence by maintaining mitochondrial ROS homeostasis [57], inhibits neural stem cells death [58], promotes bone marrow cell-mediated angiogenesis in post-myocardial infarction [59]. These evidences demonstrate that SIRT3 is the potential target for enhancing stem cell viability and function.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroblastoma SH-SY5Y cells were pretreated with the conditioned medium extracted from rat adipose tissue-derived MSCs (AT-MSCs) to check MSCs conditioned media's effect on pro-oxidizing agents. Neuroblastoma cells cocultured with conditioned media showed more decreased mortality and ROS generation when treated with H2O2 or 6-OHDA (6-hydroxydopamine), a dopaminergic selective toxin; than Neuroblastoma cells not preconditioned with conditioned media (166). MSCs conditioned medium is a good therapeutic candidate as neural stem cells, pretreated with conditioned medium (CM-NSCs) showed increased survival and enhanced migratory activity; but NSCs alone lacked these extra characteristics (167).…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…The incorporation of growth factors, such as brain-derived growth factor (BDNF), neurotrophin-3 (NT-3), neurotrophin-4/5 (NT-4/5), growth/differentiation factor 5 (GDF5) and GDNF, has been investigated for their potential to improve dopaminergic cell transplantation strategies (Clayton & Sullivan, 2007;Feng et al, 1999;Hyman et al, 1994;Jaumotte & Zigmond, 2014;Lin, Doherty, Lile, Bektesh, & Collins, 1993). While they have all shown to improve dopamine neuron survival in VM cultures, GDNF has been established as an extremely potent neurotrophic factor, significantly improving cell survival and efficacy (Apostolides, Sanford, Hong, & Mendez, 1998;Chaturvedi et al, 2003;Deng et al, 2013;Redmond et al, 2013;Rosenblad, Martinez-Serrano, & Bjorklund, 1996;Yurek, Flectcher, Kowalczyk, Padegimas, & Cooper, 2009).…”
Section: Growth Factor Provisionmentioning
confidence: 99%
“…Hydrogels from a variety of sources, both natural and synthetic, have shown to successfully deliver trophic factors to the brain in a site-specific, controlled and sustained manner (Chierchia et al, 2017;Fon et al, 2014;Li et al, 2016). Further to the enhanced delivery of GDNF in injectable hydrogels (Fon et al, 2014), many approaches have investigated the use of hollow microparticles to achieve sustained GDNF release from a single administration (Agbay, Mohtaram, & Willerth, 2014;Garbayo et al, 2016;García-Caballero et al, 2017;Lampe, Kern, Mahoney, & Bjugstad, 2011).…”
Section: F I G U R E 1 Therapeutic Concept Of Biomaterials For Brain mentioning
confidence: 99%